2015
DOI: 10.17016/feds.2015.075
|View full text |Cite
|
Sign up to set email alerts
|

Does Salient Financial Information Affect Academic Performance and Borrowing Behavior among College Students?

Abstract: While rising student loan debt can plague college students future finances, few federal programs have been instituted to educate college students on the mechanics of student loan borrowing. This paper exploits a natural experiment in which some students received "Know Your Debt" letters with incentivized offers for one-on-one financial counseling. Montana State University students who reached a specific debt threshold received these letters; University of Montana students did not. We use a difference-in-differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This paper includes results from a randomized eld experiment that evaluates a lowintensity informational intervention aimed at helping college students make informed and active student loan decisions. While there are some modest behavior changes among some student subgroups, there are substantially smaller borrowing eects across all students in comparison with other more intensive institution-based initiatives related to student borrowing (Kennedy, 2015;Schmeiser et al, 2015). This suggests that information alone is not sucient to drive systematically dierent borrowing choices among students and that other supports are likely necessary to aect behavior.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This paper includes results from a randomized eld experiment that evaluates a lowintensity informational intervention aimed at helping college students make informed and active student loan decisions. While there are some modest behavior changes among some student subgroups, there are substantially smaller borrowing eects across all students in comparison with other more intensive institution-based initiatives related to student borrowing (Kennedy, 2015;Schmeiser et al, 2015). This suggests that information alone is not sucient to drive systematically dierent borrowing choices among students and that other supports are likely necessary to aect behavior.…”
Section: Discussionmentioning
confidence: 98%
“…The experiment in this study situates itself in the context of initiatives by universities to decrease the borrowing of their students (Kennedy, 2015;Schmeiser et al, 2015), and from which laws have been enacted based on reported ndings.…”
Section: Introductionmentioning
confidence: 99%
“…College academic integration and financial aid receipt exhibit differential effects on entering engineering (Xueli Wang, 2013). The financial information students borrowing behaviour and academic performance (Schmeiser, Stoddard, & Urban, 2015). Lastly poverty impact attendance (E. Chen,…”
Section: Academic Adaptationmentioning
confidence: 99%